Exploring bonding and attachment in Aboriginal families - Nikia Bailey; Yvonne Clark (Australian Journal of Psychology)
Objective Bonding and attachment relationships are essential to how children develop in society. These relationships have primarily been understood through the “Attachment Theory” which frames parent-child relationships, and the ways a child can be supported to develop within a secure base. Attachment theory (M. D. S. Ainsworth, 1978; Bowlby, 1969), has extensive literature supporting its application, however, its roots are heavily tied to Eurocentric familial understandings (Choate & Tortorelli, 2022).This paper explores the experiences and knowledges of Aboriginal and culturally competent non-Aboriginal mental health professionals in relation to bonding and attachment via three research questions focused on how they conceptualise bonding and attachment, what they think needs to be better understood, and how accurately they think Attachment theory encapsulates Aboriginal family dynamics.Method Eight participants were interviewed using the yarning method (Bessarab & Ng’andu, 2010) to collect qualitative data for this study. Through the participant’s work, study, cultural background and own life experiences, they conveyed information about parenting and attachment relationships. Thematic analysis was utilised to identify patterns amongst the participants’ responses.Results Participants spoke to bonding and attachment in Aboriginal families in the following ways: Intergenerational Trauma, Ongoing Colonisation, Collectivist Culture, Connection to Country, Self-Determination, and Rejection of Deficit Framework. Together, these findings contribute to the conceptualisation of bonding and attachment in Aboriginal families from the perspective of Aboriginal and culturally competent non-Aboriginal mental health professionals.Conclusion This exploration expands on the limited knowledge about bonding and attachment for Aboriginal people and highlights their views from a cultural lens involving kinship and community systems which can deviate from the Western conception of bonding and attachment.